A Qualitative Study of Risk and Protective Factors for Resilience in Survivors of Sex Trafficking - Knight, Logan (Violence against women, 2023)
This study explored risk and protective factors for resilience in survivors of sex trafficking from the survivors’ perspectives. In-depth interviews were conducted with 16 participants recruited from survivor-led advocacy agencies and social service agencies that provide trafficking-specific services. Two overarching themes emerged from data analysis: (a) deep connections to self and others facilitate resilience and (b) detrimental “help” threatens survivors’ resilience. Our findings suggest that it may be important for service providers to assist survivors build healthy relationships with themselves and others to promote survivors’ resilience. Further, our results highlight the importance of offering more inclusive, survivor-centered, and trauma-informed services.